Sweden : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the findings of the Financial System Stability Assessment for Sweden. The Swedish financial system is large and highly interconnected, putting a premium on the accompanying policy framework. Relative to the size of the domestic economy, the financial system is among Europe's largest. It features complex domestic and international linkages, reflecting Sweden's role as a regional financial hub. However, the macrofinancial risks have grown since 2011, for example the rising share of highly indebted households. Stress tests also suggest that banks and nonbanks are largely resilient to solvency shocks, but concerns persist about the ability of bank models to capture unexpected losses.